Automatic Transformer Cooling System Using PLC - Bharathidasan, S.; Balamurugan, N.; B. Susithra; M. Nishad; B. Sankar (Asian Journal of Electrical Sciences, 2019)
In the previous 20 years transformer warming is a noteworthy issue in creating station, substation, circulation locale and different territories. The primary driver of overheating are Insulation overheating, Corona overheating, Liquid overheating, Arcing is overheating, screen testing overheating. Because of this it causes numerous issues, for example, Coil harm, bursting of transformer, Block of wind, and so forth. To lessen the warmth which is created from the transformer, to trip the transformer when it is in over warmth condition and the stop the absolute circuit for upkeep period a we have built up this task dependent on Programmable Logic Controller.